Application of the Problem Based Learning (PBL) Model with Audio Visual Media to Increase Motivation and Learning Outcomes of Mathematics on Decimal Number Material for Grade IV Students of SD Negeri 5 Bumirejo Academic Year 2022/2023 - Inayatul Masykuroh; Rokhmaniyah Rokhmaniyah; Wahyudi Wahyudi (Universitas Sebelas Maret, 2023)
The study aimed to describe the steps for implementing Problem Based Learning with audio-visual media to increase motivation and mathematics learning outcomes, and describe the constraints and solutions in learning with audio visual media. The subjects were teachers and fourth grade students at SDN 5 Bumirejo. The data were qualitative and quantitative. Data collection techniques were observation, interviews, and tests. Data validity used triangulation of sources and triangulation of techniques. Data analysis included data reduction, data presentation, and drawing conclusions. The interview on students’ learning motivation in mathematics about decimals described 57.66% in the first cycle, 70.06 in the second cycle, and 87.40% in third cycle. The students’ learning outcomes increased 70.73% in the first cycle, 79.63% in the second cycle, and 88.89% in the third cycle. It concludes that the implementation of Problem Based Learning with audio visual media improves motivation and mathematics learning outcomes about decimals to fourth grade students of SDN 5 Bumirejo in academic 2022/2023